(untitled) (Research, Society and Development, 2021)
Introduction: Diabetes Mellitus (DM) establishes an important obstacle for public health, remaining related to the qualification of Basic Health Units (UBS). As it is a chronic disease, DM can cause damage without the possibility of being reversed and which reflect negatively on the life conditions of individuals affected by this pathology. As a result of inadequate care, damage may occur in the extremities of the carrier of this pathology. It is especially in the basic units where health care workers need to develop techniques that make care plans feasible to assist in the contribution of adequate care and disease prevention. Objective: To identify through the study the difficulties faced by professionals and describe what are the possible solutions to facilitate care for the person affected by DM in primary care. Methodology: This is a qualitative approach study, of the integrative review type, which is part of the six-step procedure, which is the identification of the theme and selection of the hypothesis, establishment of the research strategy, definition and data collection, data analysis collected, interpretation and presentation of results, which will address the care of diabetic foot in primary care. The strategy of identification and selection of articles originated through the search for the Virtual Health Library (VHL), with access to the following electronic databases such as Latin American and Caribbean Literature in Health Sciences (LILACS), Medical Literature Analysis and Retrieval System Online (MEDLINE), Nursing Database (BDENF) and Scientific Electronic Library Online - Electronic Scientific Library Online (SCIELO). Manual searches were also carried out on the reference lists of selected articles in March 2021. The following descriptors in health sciences (DeCS) were used: Diabetes mellitus; Diabetic foot; Primary care and use of the “and” boleador. The following inclusion criteria were adopted for the selection of articles: complete materials, in Portuguese and English, in article format and with a time frame from 2010 to 2020. The exclusion criteria were duplicate, incomplete articles that did not meet the theme of the study. Results: After thorough research, two categories were found: 1- The importance of preventing injuries to the diabetic foot to avoid irreversible damage to health and 2- The understanding of the diabetic public regarding foot care. Final Considerations: At the end of the research, it was possible to conclude the importance of the assistance provided by nurses to diabetic patients in Primary Health Care. Their role goes far beyond assessing the general condition of the client, but there is also an educator role.